2018
DOI: 10.1016/j.yhbeh.2017.09.017
|View full text |Cite
|
Sign up to set email alerts
|

Effects of maternal or paternal bisphenol A exposure on offspring behavior

Abstract: Bisphenol A (BPA) is an endocrine disrupting chemical used in the production of polycarbonate plastics and resins. Exposure to BPA during gestation has been proposed as a risk factor for the development of neurobehavioral disorders, such as autism spectrum disorder. To address the behavioral impact of developmental exposure to BPA, we tested offspring of mice exposed to a daily low dose of BPA during pregnancy. We also asked if preconception exposure of the sire affected behaviors in offspring. Sires that cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 93 publications
3
22
0
Order By: Relevance
“…In rodents, the male is more likely to initiate contact with the mother and in turn, licking and grooming from the dam toward their male offspring is usually more important and fundamental for the male for develop appropriate sociosexual interaction later in life (Moore, 1984;Della Seta et al, 2005;Porrini et al, 2005). Early EDC exposures that disrupt these features may alter the offspring's ability to stimulate maternal care, yet few studies have examined the effects of EDCs on olfaction or ultrasonic vocalizations (see however Harris et al, 2018;Krishnan et al, 2019). Cross fostering studies seem to confirm this hypothesis as the behavioral outcome (social response and anxiety) of juvenile male and female mice was not only affected by BPA exposure but also by early interaction with the biological or foster non exposed dam (Cox et al, 2010).…”
Section: Edcs: What Is Next For Maternal Studies?mentioning
confidence: 99%
“…In rodents, the male is more likely to initiate contact with the mother and in turn, licking and grooming from the dam toward their male offspring is usually more important and fundamental for the male for develop appropriate sociosexual interaction later in life (Moore, 1984;Della Seta et al, 2005;Porrini et al, 2005). Early EDC exposures that disrupt these features may alter the offspring's ability to stimulate maternal care, yet few studies have examined the effects of EDCs on olfaction or ultrasonic vocalizations (see however Harris et al, 2018;Krishnan et al, 2019). Cross fostering studies seem to confirm this hypothesis as the behavioral outcome (social response and anxiety) of juvenile male and female mice was not only affected by BPA exposure but also by early interaction with the biological or foster non exposed dam (Cox et al, 2010).…”
Section: Edcs: What Is Next For Maternal Studies?mentioning
confidence: 99%
“…The GEN concentration has previously been shown to affect various parameters in mice 56‐58 and to result in circulating concentrations similar to those in humans consuming soy‐rich diets 59 . We, and others, have demonstrated that the LD and UD of BPA cause various behavioural disruptions in rodent models 21‐23,32,60‐62 . At weaning, one male and one female pup from each litter were analysed for the parameters below (n = 6 males and 6 females/treatment group).…”
Section: Methodsmentioning
confidence: 99%
“…Exposure to a regular low-dose of BPA during pregnancy tested offspring of mice. Mice who were exposed had offspring that had increased anxiety-like behavior [ 64 ].…”
Section: Influence Of Estrogenic Endocrine Disruptors Exposure On mentioning
confidence: 99%